Evaluation of internal control in supporting the sales accounting information system of PT. Trans Retail Indonesia Buah Batu Transmart branch - Muhtarudin, Muhtarudin; Nurhayati Pertiwi (SEAN Institute, 2024)
The evaluation of internal controls over the sales accounting information system is a highly important process to ensure that a company's operations run efficiently, accurately, and securely, especially when involved in the retail and sales business. This research aims to evaluate the impact of using the Sales Accounting Information System on internal sales controls. The study seeks to assess the extent to which the implementation of this information system affects the effectiveness of internal controls in the sales context. The research method employed is qualitative descriptive research, which can provide in-depth insights into internal controls within the sales accounting information system and serve as a strong foundation for necessary improvement recommendations. Data is collected through qualitative data collection techniques, including interviews with personnel involved in the sales accounting information system and auditors, as well as the collection of data from internal documentation such as policies, procedures, internal reports, or internal control records. Positive outcomes from the evaluation of internal controls over the sales accounting information system can offer various benefits to the company and relevant stakeholders. Some potential positive outcomes that may arise from this research include Improved Operational Efficiency, Enhanced Financial Information Reliability, Enhanced Stakeholder Trust, Prevention of Fraud and Risks, Legal Compliance, Cost Efficiency, Positive Company Reputation: Building a positive company reputation. These positive outcomes underscore the importance of evaluating internal controls within the sales accounting information system for the overall success and integrity of the business operations.